การตรวจหาเชื้อรา Cryptococcus neoformans จากมูลนกภายในบริเวณมหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ (ISOLATION OF CRYPTOCOCCUS NEOFORMANS FROM AVIAN DROPPING AT SRINAKHARINWIROT UNIVERSITY ONGKHARAK CAMPUS) - บุบผัน ภัทธกร; โสมทัศน์ อภิสรา; จินพุทธ พรสวรรค์; ประมงคล ณัฐชาติ; ศรีธวัชพงศ์ อนุกูล (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2017)
Cryptococcosis คือ โรคติดเชื้อที่เกิดจากเชื้อรา Cryptococcus neoformans ส่งผลให้เสียชีวิตได้ การติดเชื้อราชนิดนี้มักก่อโรคเยื่อหุ้มสมองอักเสบพบมากในผู้ป่วยที่มีภาวะภูมิคุ้มกันบกพร่อง การศึกษานี้มีวัตถุประสงค์เพื่อตรวจหาเชื้อ C. neoformans จากมูลนกตามอาคารภายในมหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ โดยเก็บตัวอย่างมูลนกทั้งหมด 161 ตัวอย่าง จากจำนวนอาคารทั้งหมด 18 แห่ง นำตัวอย่างมาทำการเจือจางที่ระดับ 10-10 ด้วยสารละลาย Phosphate Buffer Saline (PBS) และเพาะเชื้อบน Sabouraud Dextrose Agar (SDA) ที่ผสม Penicillin G Sodium ทำการพิสูจน์บน Cryptococcus Differential Agar แล้วนำโคโลนีที่สงสัยไปย้อมด้วย India Ink ทดสอบคุณสมบัติการสร้างเอนไซม์ Urease ด้วย Urea Base Agar และเอนไซม์ Phenol Oxidase ด้วย Caffeic Acid Agar เพื่อเป็นการยืนยันเชื้อ ผลการศึกษาพบเชื้อ C. neoformans 52 ตัวอย่าง คิดเป็นร้อยละ 32.29 คณะสหเวชศาสตร์ หอพักบุคลากรศูนย์การแพทย์ อาคารสโมสร และหอพระ มีอัตราการตรวจพบเชื้อมากที่สุดคิดเป็นร้อยละ 50 ส่วนบริเวณเรือนไทยหมู่ ธ ทูลกระหม่อมแก้ว ตรวจไม่พบเชื้อในครั้งนี้ ผลที่ได้แสดงให้เห็นว่าสามารถตรวจพบเชื้อ C. neoformans จากมูลนกภายในมหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ ซึ่งเป็นข้อบ่งชี้ให้เห็นถึงความจำเป็นในการส่งเสริมให้มีการป้องกันและควบคุมการติดเชื้อ C. neoformans นอกจากนี้การศึกษานี้จะเป็นประโยชน์ต่อการพัฒนาแผนสุขาภิบาลเพื่อจัดการกับมูลนกในพื้นที่ของมหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ อีกด้วย คำสำคัญ: คริปโตค็อคคัส นีโอฟอร์แมนส์ โรคเยื่อหุ้มสมองอักเสบ มูลนก มหาวิทยาลัยศรีนครินทรวิโรฒ องครักษ์ Cryptococcosis is a fungal infection caused by Cryptococcus neoformans, a life-threatening infection that is usually manifested as menigeoencephalitis mainly in immunocompromised patients. The objective of this study was to investigate C. neoformans in avian droppings from buildings in the Srinakharinwirot University, Ongkharak campus. A total of one hundred and sixty–one sample of avian droppings was collected from 18 buildings in different regions in Srinakharinwirot University, Ongkharak campus. Each sample was diluted to 10-10 with phosphate buffer saline (PBS) solution and then cultured in Sabouraud dextrose agar medium including Penicillin G sodium. Identification of C. neoformans was performed on the basis of different colonies on Cryptococcus differential agar, presence of capsule on India ink preparation, ureas production of urea base agar medium, phenoloxidase production of Caffeic acid agar medium was also used to confirm C. neoformans. Results of the fungus isolated from 161 samples showed that 52 (32.29%) were positive with C. neoformans. The highest frequency was observed in the droppings from Faculty of Health Science, Medical, nursing student Dormitory, Ongkharak Club, and the Buddha Shrine (50%). Thai wisdom museum not found of C. neoformans in pigeon droppings. The result suggested that C. neoformans were present in avian droppings in the Srinakharinwirot University, Ongkharak campus. Indicated that, it is necessary to have a compaign for prevention and control of C. neoformans infection. In addition, this work will be useful in developing a sanitation plan at the Srinakharinwirot University to handle avian droppings in the campus. Keywords: Cryptococcus neoformans, Cryptococcal Meningitis, Bird Dropping, Srinakharinwirot University Ongkharak Campus